The Importance of Trust and Deliberation In Leadership From A Hadith Perspective - Chaliddin Chaliddin; Munawar Khalil (Ma'had Aly Raudhatul Ma'arif, 2025)
Leadership (imamah) in Islam plays a vital role in maintaining the ummah's social order, justice, and moral integrity. This study aims to explore the hadiths concerning the mandate and responsibility of Islamic leaders, particularly focusing on the principles of shura (consultation) and amanah (trust), and to contextualise them within modern leadership theories. Using a qualitative library research method, this paper conducts a thematic and comparative analysis of prophetic traditions related to leadership. It examines their relevance in light of contemporary theories such as deliberative democracy and ethical leadership. The findings show that while the Qur'an does not explicitly mention